Corticosteroid therapy for liver abscesses in a neonate with Chronic granulomatous disease - Azadeh Darabi; Gholamali Mamouri; Hassan Boskabadi; Mohammad Saeed Sasan; Nasim Pouralizadeh; Elahe Heidari; Raheleh Faramarzi (Elsevier, 2021)
Chronic granulomatous disease (CGD) is a rare inherited immunodeficiency disorder, characterized by susceptibility to recurrent infections, including hepatic abscess. These abscesses are typically resistant to antibiotics and surgical procedures.Here, we describe an infant with CGD and liver abscesses that was successfully treated with corticosteroids and antibiotics. A 19-day-old neonate was admitted after presenting with malaise, fever, poor feeding, abdominal distension, and hepatomegaly. Routine laboratory evaluation for sepsis and polymerase chain reaction (PCR) testing for SARS-CoV-2 was done. The PCR test results was negative in two different samples 15 days apart. Ultrasound image showed numerous focal hypoechoic masses in the liver suspected to liver abscess. Nitroblue tetrazolium (NBT) test was sent which showed less than 5% positive leukocytes. The neonate recovered completely, and the liver abscesses were removed once oral prednisolone was started in combination with antibiotic therapy.Corticosteroid therapy and prolonged antibiotic courses can be effective for the management of CGD-related hepatic abscesses.